2007
DOI: 10.1002/mus.20943
|View full text |Cite
|
Sign up to set email alerts
|

Changes in short afferent inhibition during phasic movement in focal dystonia

Abstract: Impaired surround inhibition could account for the abnormal motor control seen in patients with focal hand dystonia, but the neural mechanisms underlying surround inhibition in the motor system are not known. We sought to determine whether an abnormality of the influence of sensory input at short latency could contribute to the deficit of surround inhibition in patients with focal hand dystonia (FHD). To measure digital short afferent inhibition (dSAI), subjects received electrical stimulation at the digit fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…We and others have shown that SAI is reduced during both the onset of muscle activity [6], [8], [9] and during sustained muscle contraction [6], [7]. Specifically, we observed reductions in SAI as early as movement preparation between an auditory “warning” and “go” cue and these reductions are likely cortically or sub-cortically mediated [6].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…We and others have shown that SAI is reduced during both the onset of muscle activity [6], [8], [9] and during sustained muscle contraction [6], [7]. Specifically, we observed reductions in SAI as early as movement preparation between an auditory “warning” and “go” cue and these reductions are likely cortically or sub-cortically mediated [6].…”
Section: Introductionsupporting
confidence: 61%
“…First, how is SAI modified when the muscle is involved versus uninvolved in the task? [8], [9]. Second, does the modulation of SAI depend on the specific digit (i.e., digit 2 versus digit 5)?…”
Section: Introductionmentioning
confidence: 99%
“…In a writer’s cramp study, SAI was observed to increase in the abductor digiti minimi muscle during phasic contraction of Flexor digitorum interrosseous (FDI) muscle, which was speculated to reflect a compensatory mechanism to prevent overflow of dystonia from the index finger to the little finger 11. Similarly an increased SAI in our study during DBS OFF possibly represented a compensatory mechanism in response to worsening of dystonia symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…At short latencies (less than 40ms) the contralateral S1 and secondary somatosensory cortex (S2) are primarily activated, while at longer latencies (more than 40ms) there is more widespread activation of sensory areas, including S1, bilateral S2, and the contralateral posterior parietal cortex [20,21]. Short latency afferent inhibition (SAI), also exhibits a somatotopic organization [22] such that cortical inhibition due to electrical stimulation of a digit near a target muscle (i.e., homotopic) is stronger than cortical inhibition due to stimulation of a digit distant from a target muscle (i.e., heterotopic)[23]. …”
Section: Standard Tms Paradigms and Basic Conceptsmentioning
confidence: 99%
“…TMS studies found that although SAI and LAI were comparable to healthy controls in focal dystonia patients,[79],[80] there was an increased homotopic digital short afferent inhibition (dSAI), during flexion of the second digit. This suggests that this process was a compensatory act to diminish overflow during movement [23]. Unlike the basal ganglia which receive sensory information indirectly, the cerebellum is a direct recipient of sensory input from the spinal cord [81].…”
Section: Tms In Dystoniamentioning
confidence: 99%